Validation of the abbreviated indicators of perceived residential environment quality and neighborhood attachment in China - Mao, Yanhui; Luo, Xinyi; Guo, Shuangyang; Xie, Mei; Zhou, Jing; Huang, Rui; Zhang, Zhen (Frontiers in Public Health, 2022)
The purpose of this research is to utilize factor analyses to evaluate the reliability and factorial structure of an abbreviated version of the instrument that includes indicators of perceived residential environment quality (PREQ) and neighborhood attachment (NA) in Chinese urban environments. The instrument has 11 scales that measure PREQ and 1 scale measuring neighborhood attachment (NA). Architectural and urban planning aspects (three scales: Architectural and Town-planning Space, Organization of Accessibility and Roads, Green Areas), socio-relational aspects (one scale: People and Social Relations), functional aspects (four scales: Welfare Services, Recreational Services, Commercial Services, and Transport Services), and contextual aspects (three scales: Pace of Life, Environmental Health, and Upkeep and Care) are all covered by the 11 PREQ scales. A total of 1,332 people living in Chinese urban cities completed a self-report questionnaire that included these 12 scales. A calibration sample and a validation sample that were randomly split from the total sample verified the factorial structures of this instrument, and the abbreviated instrument had acceptable reliability and validity. The validated abbreviated version of the PREQ and NA instruments allowed for a more reliable and manageable tool that might lessen respondents' exhaustion of a large number of items, this also contributed to the policy-making for urban planning and practical architectural design.